Neutrophil-lymphocyte, platelet-lymphocyte and lymphocyte-monocyte ratios may not be useful markers to assess disease activity in rheumatoid arthritis: A STROBE-compliant article. Issue 45 (12th November 2021) - Lijuan, Wang; Yuting, Zhou; Chaoyang, Liang; Ju, Yang
Abstract : Abstract: The associations among the neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and lymphocyte-monocyte ratio (LMR) and disease activity in rheumatoid arthritis remains unclear. To evaluate these indicators as potential markers of disease activity in patients with rheumatoid arthritis (RA). This cross-sectional study included 547 adult patients with RA. The patients were divided into two groups according to the disease activity score (DAS) system: remission and disease activity. Differences in the NLR, PLR and LMR of the two groups were assessed. Correlations were analyzed using Spearman analysis, and receiver operating characteristic (ROC) curves were used to identify the sensitivity, specificity, and optimal cutoff values to differentiate active RA patients from inactive RA patients. There was a statistically significant difference in the NLR (4.2 ± 3.2 vs 3.4 ± 2.4, P = .034) and PLR (222.3 ± 136.4 vs 176.9 ± 89.8, P = .006) between the two groups, but not for the LMR (3.0 ± 1.8 vs 3.4 ± 2.4, P = .115). In addition, the DAS28 and traditional inflammatory markers, including ESR and CRP, were weakly positively correlated with the NLR and PLR. Based on the ROC curves, the NLR (sensitivity 31.8%, specificity 77.8%) and PLR (sensitivity 57.3%, specificity 63.9%) were less valuable than the ESR (sensitivity 67.2%, specificity 91.7%) and CRP (sensitivity 76.2%, specificity 91.7%) for differentiating inactive RA patients from active RA patients due to low sensitivity and specificity and combining NLR or PLR also cannot significantly improved the diagnostic value of ESR and CRP. NLR, PLR and LMR may not be an useful independent diagnostic or complementary marker for disease activity in RA patients.